Melacak Peranan Tujuan Pendidikan dalam Perspektif Islam - Asmal May (TSAQAFAH, 2015)
Education is an activity supposed to improve entire aspects of human personality that lasts a lifetime, so its process is not only formal but also informal. It may be going inside or outside the class. Education, in other side is a development of human potentials process which is easily influenced by environment and habits whereas students live and thrive. As well as Islamic education, which has its own characteristics compared with another concepts of education is a kind of manifestation from Muslim aim to conserve, transform, and internalize Islamic value to the future generation in Islam community, so that culture-religious aspired could be able to function and improve in the community all the time as well. The goal of Islamic education in general is centered to the efforts to establish “Insân Kâmil” (Perfect Human) with several indicator as follows: become servant of Allah, become khalifah, become mercy (rah}mah) to the universe, become uswah h}asanah, and for welfare as well. This general goal is absolute, unchanged, and generally accepted, due to its association with concept of Islam inheriting absolute and universal truth. This paper will discuss the sources and main goal of Islamic education with another specific and temporary goal besides it, and also discuss about the characteristics of Islamic education.